2021
DOI: 10.1055/s-0041-1741086
|View full text |Cite
|
Sign up to set email alerts
|

To Study Acute Changes in Brain Oxygenation on MRI in Healthcare Workers Using N95 Mask and PPE Kits for Six Hours a Day

Abstract: Background Due to long working hours wearing an N95 mask and PPE kit during the COVID-19 pandemic, the healthcare workers (HCWs) complained of headaches, confusion, and exhaustion. This study was therefore performed to study the changes in brain oxygenation. Aim To compare brain oxygenation in health care workers wearing an N95 mask with a PPE kit versus a three-ply mask during an intensive care setting for 6 hours. Materials and Methods Thirty clinicians and 30 paramedical staff participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…In patients with aneurysms or brain tumours this phenomenon could be deleterious. Another study showed a pathologic and altered brain metabolism while wearing a N95 mask for 6 hours 11 . The MRI imaging revealed a significant drop in brain oxygenation.…”
Section: Possible Sub-threshold Impact Of Masks -The Low-dose Long-te...mentioning
confidence: 97%
See 1 more Smart Citation
“…In patients with aneurysms or brain tumours this phenomenon could be deleterious. Another study showed a pathologic and altered brain metabolism while wearing a N95 mask for 6 hours 11 . The MRI imaging revealed a significant drop in brain oxygenation.…”
Section: Possible Sub-threshold Impact Of Masks -The Low-dose Long-te...mentioning
confidence: 97%
“…retention of bacteria during surgical wound care and operations, at present the question needs to be addressed as to the long-term effects widespread mask wearing may have on normal breathing. It is noteworthy that the compulsory wearing of masks for the entire population provided good research conditions and consequently numerous publications dealing with the adverse effects of mask wearing [4][5][6][7][8][9][10][11] . Various volatile metabolites are produced from in vivo biochemical and metabolic pathways and their concentrations in exhaled breath provide immediate physiological 12,13 , metabolic 14,15 and pathological 16,17 magnitudes with the possibility of monitoring various processes and interventions including therapies 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Headache was the most common symptom in both groups in their study. In addition, clinical symptoms such as nausea, vomiting, dizziness, blurred vision, drowsiness and fatigue were observed more frequently in N95 group, but also in the group using both types of masks [14].…”
Section: Discussionmentioning
confidence: 90%
“…The most remarkable study among the studies conducted to date is the study of Vakharia et al on sixty volunteers [14]. The authors conducted two groups, the three-ply mask and N95 mask group in which brain oxygenation was evaluated with cerebral blood oxygenation level dependent magnetic resonance imaging (BOLD MR) at the beginning of the shift and at the end of the six-hour shift.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation